Physical, thermal and tensile behaviour of 3D printed kenaf/PLA to suggest its usability for ankle–foot orthosis – a preliminary study. Issue 8 (29th March 2022) - Shahar, Farah Syazwani; Hameed Sultan, Mohamed Thariq; Safri, Syafiqah Nur Azrie; Jawaid, Mohammad; Abu Talib, Abd. Rahim; Basri, Adi Azriff; Md Shah, Ain Umaira
Abstract : Purpose: This paper aims to discuss the physical and thermal properties of the three-dimensional (3D) printing natural composite filament, as well as the tensile behaviour of the printed composites to get an insight of its possibility to be used as an ankle–foot orthosis (AFO) material. Design/methodology/approach: Physical test that was conducted includes scanning electron microscopy analysis, thermogravimetric/differential scanning calorimetry analysis as well as the effect of fibre load after extrusion on the filament morphology. Tensile test was conducted with different amounts of fibre loads (0, 3, 5 and 7 Wt.%) on the printed specimens. Findings: There is an increment of strength as the fibre load is increased to 3 Wt.%; however, it decreases significantly as it is increased to 5 and 7 Wt.% because of the presence of voids. It also shows that the extrusion temperature severely affects the structure of the filaments, which will then affect the strength of the printed composites. Based on the results, it is possible to use kenaf/polylactic acid (PLA) filament to print out AFO as long as the filament production and printing process are being controlled properly. Originality/value: The unique aspect of this paper is the investigation of kenaf/PLA filament as a material for 3D printing, as well as its material consideration for AFO manufacturing. This paper also studies the effect of extrusion temperature on the morphological structure of the filament and its effect on the tensile properties of the printed kenaf/PLA specimen.